Molecular and functional characterization of GAD67-expressing, newborn granule cells in mouse dentate gyrus - Cabezas, Carolina; Irinopoulou, Theano; Cauli, Bruno; Poncer, Jean Christophe (Frontiers in Neural Circuits, 2013)
Dentate gyrus granule cells (GCs) have been suggested to synthesize both GABA and glutamate immediately after birth and under pathological conditions in the adult. Expression of the GABA synthesizing enzyme GAD67 by GCs during the first few weeks of postnatal development may then allow for transient GABA synthesis and synaptic release from these cells. Here, using the GAD67-EGFP transgenic strain G42, we explored the phenotype of GAD67-expressing GCs in the mouse dentate gyrus. We report a transient, GAD67-driven EGFP expression in differentiating GCs throughout ontogenesis. EGFP expression correlates with the expression of GAD and molecular markers of GABA release and uptake in 2-4 weeks postmitotic GCs. These rather immature cells are able to fire action potentials and are synaptically integrated in the hippocampal network. Yet they show physiological properties that differentiate them from mature GCs. Finally, GAD67-expressing GCs express a specific complement of GABAA receptor subunits as well as distinctive features of synaptic and tonic GABA signaling. Our results reveal that GAD67 expression in dentate gyrus granule cells is a transient marker of late differentiation that persists throughout life and the G42 strain may be used to visualize newborn GCs at a specific, well-defined differentiation stage.